DRP1 Promotes BRAFV600E-Driven Tumor Progression and Metabolic Reprogramming in Colorectal Cancer - Padder, Rayees Ahmad; Bhat, Zafar Iqbal; Ahmad, Zaki; Singh, Neetu; Husain, Mohammad (Frontiers in Oncology, 2021)
Background: Mitochondria are highly dynamic organelles which remain in a continuous state of fission/ fusion dynamics to meet the metabolic needs of a cell. However, this fission/ fusion dynamism has been reported to be dysregulated in most cancers. Such enhanced mitochondrial fission is demonstrated to be positively regulated by some activating oncogenic mutations; such as those of KRAS or BRAF , thereby increasing tumor progression/ chemotherapeutic resistance and metabolic deregulation. However, the underlying mechanism(s) are still not clear, thus highlighting the need to further explore possible mechanism(s) of intervention. We sought to investigate how BRAF driven CRC (colorectal cancer) progression is linked to mitochondrial fission/fusion dynamics and whether this window could be exploited to target CRC progression. Methods: Western blotting was employed to study the differences in expression levels of key proteins regulating mitochondrial dynamics, which was further confirmed by confocal microscopy imaging of mitochondria in endogenously expressing BRAFWT and BRAFV600E CRC cells. Proliferation assays, soft agar clonogenic assays, glucose uptake/lactate production, ATP/ NADPH measurement assays were employed to study the extent of carcinogenesis and metabolic reprograming in BRAFV600E CRC cells. Genetic knockdown (shRNA/ siRNA) and/or pharmacologic inhibition of Dynamin related protein1/Pyruvate dehydrogenase kinase1 (DRP1/PDK1) were employed to study the involvement and possible mechanism of these proteins in BRAFV600E driven CRC. Statistical analyses were carried out using Graph Pad Prism v 5.0, data was analyzed by unpaired t-test and two-way ANOVA with appropriate post hoc tests. Results: Our results demonstrate that BRAFV600E CRC cells have higher protein levels of mitochondrial fission factor- DRP1/pDRP1S616 leading to a more fragmented mitochondrial state compared to those harboring BRAFWT. This fragmented mitochondrial state was found to confer glycolytic phenotype, clonogenic potential and metastatic advantage to cells harboring BRAFV600E. Interestingly, such fragmented mitochondrial state seemed positively regulated by mitochondrial PDK1 as observed through pharmacologic as well as genetic inhibition of PDK1. Conclusion: In conclusion, our data suggest that BRAF driven colorectal cancers have fragmented mitochondria which confers glycolytic phenotype and growth advantage to these tumors, and such phenotype is dependent at least in part on PDK1- thus highlighting a potential therapeutic target.